The Existence of Chinese Language in The Globalization Era - Murtadhoh, Nuzulul Luthfi; Arini, Wulan (Confucius Institute Universitas Sebelas Maret, 2023)
In an era of globalization marked by ever-stronger digital connectivity and close economic growth, languages play an important role in cross-cultural communication and international trade. Mandarin, being the official language of the People's Republic of China and the mother tongue of approximately one billion individuals worldwide, is one language that has a prominent role in this context. This article discusses the existence of Mandarin in the era of globalization. Mandarin is quite important in the context of the global economy, in line with the rapid economic growth in China, which is becoming a very influential world economic power. This article is written using a qualitative method by using supporting literature such as books and journals. Globalization brings real business and cultural exchange opportunities, and Mandarin holds the key to maximizing the benefits of these opportunities. The findings of this study are that many language learners are interested in learning Mandarin. In addition, the popularity of Chinese as the second most spoken language outside of China continues to increase, especially in education in schools and language study centres worldwide. Nevertheless, the existence of Mandarin Chinese also faces various obstacles and barriers in the era of globalization. Despite these obstacles, the potential and opportunities in intercultural communication, global economy, and diplomacy continue to grow. Overall, the Chinese have an increasingly important role in the era of globalization. It reflects the ongoing global changes and the importance of cross-cultural understanding to maintain world peace in an increasingly connected world.